Clinico-histopathological analysis of orbito-ocular lesions: a hospital-based study - Kafle, Santosh Upadhyaya; Singh, Mrinalini; Kafle, Prerna Arjyal; KC, Bal Kumar; Yadav, Sanjeev Kumar; KC, Anadi Khatri (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Preoperative diagnosis of orbital and ocular lesions is necessary for optimum treatment. The study aims to analyze the histomorphological spectrum of orbito-ocular lesions and to evaluate the need of ancillary techniques for confirmation of diagnosis.Methods: A cross sectional hospital based study of orbito-ocular surgical biopsy samples obtained in the Department of Pathology, at Birat Medical College Teaching Hospital, Nepal during one-year period was analysed for clinical and histopathological findings. Demographic data, site and tissue type, benign or malignant, recommendations for special stains and immunohistochemistry panel study were analysed.Results: Out of 185 total samples, male to female ratio of 1.1:1, age ranged from ten month to 82 years, 11-20 year age group had 39 (21.1%) orbito-ocular lesions and cornea-conjunctiva was involved in 104 (56.2%). Clinical diagnosis correlated well with histopathological diagnosis, p